Lens induced glaucoma in a tertiary eye care centre in Western Nepal - Shrestha, Ruchi; Godar, Manita Sunam; Gurung, Shanti; Devkota, Prativa; Manandhar, Laxmi Devi; Shrestha, Nirsara (Nepalese Journal of Ophthalmology, 2019)
Introduction: Lens induced glaucoma due to hypermature cataracts is an important cause of secondary glaucoma in the developing world. The most common etiology of lens induced glaucoma is phacomorphic glaucoma from untreated senile cataract.Objectives: To study the demographics, clinical presentations and surgical outcome of lens induced glaucoma (LIG).Materials and methods: It is the prospective case series of fifty three patients eyes with LIG over a 6 months period from June 2015 to November 2015. All cases of lens induced glaucoma underwent cataract surgery. Data including demographics, clinical presentations, surgical outcome were analysed using Statistical Package for Social Studies 20.0.Results: The mean age was 61.5 years (Standard deviation 8.9) with predominantly women (30, 56.6%) were affected. Phacomorphic glaucoma (38, 71.7%) was the main cause of lens induced glaucoma, followed by phacolytic glaucoma (15, 28.3%). The main clinical symptoms were reduced vision (100%), eye pain (96.2%) and redness of eyes (62.3%). All patients (100%) presented with visual acuity of 6/18 as noted in 16(30.2%) cases.Conclusions: The main clinical presentations of LIG are triad of acute reduced vision, eye pain and redness. The better final BCVA is found when there is an early presentation and less IOP at the time of presentation Public awareness, early detection and early intervention aids in good visual recovery and control of intraocular pressure in LIG.